Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.1016/j.jmacro.2005.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Optimal simple rules for the conduct of monetary and fiscal policy

Abstract: Zh ghyhors d vlpsoh prgho iru vwxg|lqj wkh lpsdfw ri prqhwdu| dqg vfdo srolflhv rq djjuhjdwh ghpdqg/ dw wkh exvlqhvv f|foh iuhtxhqflhv1 Zh irfxv rq wzr txhvwlrqv sulqflsdoo|1 Iluvw/ zkdw duh wkh nh| surshuwlhv ri wkh mrlqw rswlpdo vlpsoh uxohv jryhuqlqj wkh frqgxfw ri wkh v|vwhpdwlf frpsrqhqwv ri prqhwdu| dqg vfdo srolf|B Vhfrqg/ iroorzlqj Eodqfkdug +4<;8, zh frqvwuxfw dq lqgh{ ri vfdo vwdqfh wr glvhqwdqjoh wkh ch{shqglwxuh* dqg zhdowk hhfwv ri vfdo srolf|1 Zh qg wkdw xqghuslqqlqj wkh vr0fdoohg cWd|oru sulqfls… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 17 publications
0
33
0
3
Order By: Relevance
“…In this direction the contribution of Chadha and Nolan (2007) according to which "conducting stabilization policy incorporates not only a set of monetary policy choices […] but also fiscal policy that gives considerable force to automatic stabilizers" 14 .…”
Section: Non Inflationary Deficit and Non-restrictive Interest Ratesmentioning
confidence: 99%
See 1 more Smart Citation
“…In this direction the contribution of Chadha and Nolan (2007) according to which "conducting stabilization policy incorporates not only a set of monetary policy choices […] but also fiscal policy that gives considerable force to automatic stabilizers" 14 .…”
Section: Non Inflationary Deficit and Non-restrictive Interest Ratesmentioning
confidence: 99%
“…The conclusions reached in these seminal contributions gave shape to the current relation between monetary and fiscal policy action in Europe. But several critical contributions such as Nordhaus (1994), Kirsanova, Stehm and Vines (2005) and Chadha and Nolan (2007) have concluded that -even in modern policy regimes under which fiscal and monetary policy are independent -economic policy in a single country gives better results if both authorities cooperate to reach their goals. Therefore results are not so unequivocal as the European mainstream asserts.…”
mentioning
confidence: 99%
“…Equation (1) gives aggregate demand, y t , as a function of this period's expectation, E t ; of demand next period, y t+1 , and of the expected real interest rate, where R t is the policy rate, E t t+1 is the next period expectation of in ‡ation and is the intertemporal rate of substitution in output. 4 Equation (2) is the forward-looking New Keynesian Phillips curve that relates current in ‡ation, t , to discounted expected next period in ‡ation, where is the subjective discount factor, and is proportional to the deviation of aggregate demand from supply, where is the slope of the Phillips curve. 5 The term is related to two deep parameters in the underlying Calvo-Yun model (see Yun, 1996): the probability of …rms maintaining a …xed price in the next period, , and the subjective discount factor, : In in ‡ation space can be shown to be equal to (1 ) (1 ) and thus in price space, with the deviation in the price level proportional to in ‡ation (see equation 6), the Phillips curve becomes:…”
Section: The Basic New Keynesian Model With Moneymentioning
confidence: 99%
“…Finally, the forward-looking Phillips curve, (2), determines the split between current and expected in ‡ation as a function of the current output gap but we can use the current in ‡ation rate to back out the price level: is the fraction of …rms that hold prices …xed and so (1 ) is the fraction which are given a signal to re-price as a mark-up over marginal costs (see Yun, 1996) thus in ‡ation is simply the ratio of …rms that reprice at the new price level, p t , relative to those that cannot re-price, (6). 6 4 This intertemporal equation also operates as the basic asset pricing equation, or kernel, in a New-Keynesian model. 5 This compares to various speci…cations of the Phillips curve through time, relating …rstly the in ‡ation rate to the unemployment rate and then the change in in ‡ation to various measures of capacity.…”
Section: The Basic New Keynesian Model With Moneymentioning
confidence: 99%
“…Ever since Leeper (1991) the literature began to relax some of the simplifying assumptions which were part of the original framework, in order to be able to study the interactions between fiscal and monetary policy in a richer and more realistic framework 2 .Basically, contributions differ insofar as they employ alternatives strategies to depart from Ricardian equivalence. One strand of literature models the presence of non-Ricardian consumers à-la Blanchard (1985), by assuming a non-zero probability of death for households (Leith and Wren-Lewis (2000), Chadha and Nolan (2007)). Under this specification, consumers'finite-horizon implies a wealth effect of government debt on aggregate consumption via the Euler equation.…”
Section: Introductionmentioning
confidence: 99%